2007
DOI: 10.1108/17410380710763886
|View full text |Cite
|
Sign up to set email alerts
|

A framework for implementing cost and quality practices within manufacturing

Abstract: PurposeThe techniques that help organisations implement leading edge cost and quality practices in manufacturing operations management are typically disparate and generic in nature. There is a need to identify integrated practices at the right level of granularity, based on a clear definition of the existing operations practices. This paper proposes a novel framework for achieving and maintaining good cost and quality operations management practice within a manufacturing environment.Design/methodology/approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Early attempts to use these performance measures to measure or evaluate the effectiveness of newer systems like lean manufacturing or lean organizations have failed. There are many studies in recent past which suggest that lean manufacturing has failed to achieve the desired results (Bhasin and Burcher, 2006;Tiwari et al, 2007;Bortolotti et al, 2015). Liker and Rother (2011) pointed out that the numerous lean programs were not successful due to the superficial approach of the organizations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early attempts to use these performance measures to measure or evaluate the effectiveness of newer systems like lean manufacturing or lean organizations have failed. There are many studies in recent past which suggest that lean manufacturing has failed to achieve the desired results (Bhasin and Burcher, 2006;Tiwari et al, 2007;Bortolotti et al, 2015). Liker and Rother (2011) pointed out that the numerous lean programs were not successful due to the superficial approach of the organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Several organizations focused on the implementation of only hard lean tools and techniques and ignored the soft lean practices (human-related practices) (Bortolotti et al, 2015;Liker and Rother, 2011). There are several reports on the lean failures caused by the misunderstanding in selection and implementation of various tools/techniques in a specific environment (Karim and Arif-Uz-Zaman, 2013;Tiwari et al, 2007). Gupta and Kundra (2012) claimed that the failure is because of the consideration of the lean as a manufacturing strategy or process, rather than as a long-term philosophy.…”
Section: Introductionmentioning
confidence: 99%
“…22 In order to assess the impact of poor assembly process, Falck et al 23 studied the assembly of 24,443 cars and found that poor assembly ergonomics caused increased risks of quality errors of several times higher for high and medium physical load assemblies. Tiwari et al 24 suggested that internal failure costs are key contribution to financial impact based on the quality model. Smallman 25 stressed on the interaction of risk management, and quality cost fraternity is needed in identifying risk and financial risk that impact management.…”
Section: Cost Of Qualitymentioning
confidence: 99%
“…The lack of appropriate performance measures has led to the conflicting results of lean implementation. There are reported failures of LM in organizations (Bortolotti et al , 2015; Behrouzi and Wong, 2011; Tiwari et al , 2007; Bhasin and Burcher, 2006). Williams et al (1992) also opine that the superiority of Japanese automobile manufacturer over Americans is due to better manufacturability, high capacity utilization, long production hours, and low wage rates in the supplier networks and not due to lean production.…”
Section: Introductionmentioning
confidence: 99%